SORPTION OF AS(V) ON GREEN RUST (FE4(II)FE2(III)(OH)12SO4 . 3H2O) AND LEPIDOCROCITE (γ-FEOOH): SURFACE COMPLEXES FROM EXAFS SPECTROSCOPY - Randall S.R.; Sherman D.M.; Ragnarsdottir K.V. (My University, 2001)
Green rust (Fe4(II)Fe2(III)(OH)12SO4 . 3H2O) is an intermediate phase in the formation of iron (oxyhydr)oxides such as goethite, lepidocrocite and magnetite; current thinking is that it occurs in many soil and sediment systems. Green rust has been shown to reduce sorbed selenate and nitrate and, therefore, might presumeably reduce sorbed arsenate to the more toxic and mobile As(III) species. We have investigated the mechanism of As(V) sorption onto green rust and its fate during oxidation of green rust to lepidocrocite. EXAFS spectroscopy was used to determine the As speciation and coordination environment. We find that As(V) is not reduced to the more mobile and toxic As(III) form following equilibrium with green rust for 24 h. It remains adsorbed as (AsO4)3- by forming inner-sphere surface complexes. The same result is obtained whether As(V) is added prior to or after green rust nucleation. Two different inner sphere surface complexes are resolved: one results from edge-sharing between AsO4 and FeO6 polyhedra while the second results from and double-corner sharing between AsO4 tetrahedra and adjacent FeO6 polyhedra. During the oxidation of green rust to lepidocrocite, the (AsO4)3- remains preferentially bound to green rust and only sorbs onto lepidocrocite when all of the green rust has been oxidized. Sorption onto lepidocrocite occurs via an inner-sphere complex resulting from bidentate corner sharing between AsO4 tetrahedra and adjacent FeO6 octahedra.